Existence and Relaxation Results for Second Order Multivalued Systems - Papageorgiou, Nikolaos S.; Vetro, Calogero (Acta applicandae mathematicae, 2021)
We consider nonlinear systems driven by a general nonhomogeneous differential operator with various types of boundary conditions and with a reaction in which we have the combined effects of a maximal monotone term A ( x ) and of a multivalued perturbation F ( t , x , y ) which can be convex or nonconvex valued. We consider the cases where D ( A ) ≠ R N and D ( A ) = R N and prove existence and relaxation theorems. Applications to differential variational inequalities and control systems are discussed.